Factors Affecting Academic Achievement of Secondary School Students in Mauritius - Atchia, Shakeel Mohammad Cassam; Chinapah, Vinayagum (Journal of Education and Research, 2019)
This paper analyses the contextualised determinants affecting the academic achievement of secondary school students in Mauritius. A mixed methodology was used to understand the effect of the determinants on students’ achievement considering the academic progression of learners from one point (CPE: Examination marking the end of primary schooling) to another (NG9A: Checkpoint assessment after three years of secondary schooling). The first phase had a non-positivist epistemological stand using the qualitative method of ‘focus group discussion’ to identify the determinants and then validate the TIMSS questionnaire. The second phase had a post-positivist epistemological stand where an amended version of the standardised international questionnaire TIMSS was administered to collect data from a sample of 600 students. The primary data were analysed to produce a Linear Multiple Regression Model. The findings reveal that 90.1% achievement can be explained by the variables of school leadership, student, socio-economic factor, and teacher (R square = 0.9.1; p < 0.05). The model shows that school leadership has a higher positive correlation on (β=0.419) students’ achievement followed by student factor (β= 0.227), tuition teacher (β= 0.154), school teacher (β= 0.117) and socioeconomic status (β= 0.048).